Suppression of polysulfides by carbonized polyacrylonitrile modified polypropylene janus separator for Li2S/r-GONR/CNT-based Li-S batteries - Deivendran, Gokul Raj; Wu, She–Huang; Wu, Yi–Shiuan; Chang, Jeng-Kuei; Jose, Rajan; Ng, Kim Hoong; Poddar, Mrinal; Sun, Chia-Liang; Yang, Chun-Chen (American Chemical Society, 2024)
Practical applications of Li2S-based Li–S batteries face two challenges that occur in both electrodes: the shuttle effect of polysulfide (PS) intermediates and the uncontrollable growth of Li dendrites. In this study, Li2S was anchored onto the surface of a two-dimensional reduced graphene oxide nanoribbon (r-GONR), which was then entangled and connected by a one-dimensional carbon nanotube (CNT)-designed carbon matrix that facilitated rapid electron transfer and physically confined Li2S. Furthermore, polyacrylonitrile (PAN)/Super P blends were used to prepare porous electrically conductive carbon composites as coating layers on a polypropylene (PP) with a bilayer structure to block PS transport and enhance conversion reaction kinetics in Li–S batteries. The resultant carbonized-polyacrylonitrile (cPAN)/Super P-coated PP Janus separators exhibited multifunctional advantages: the porous conductive cPAN/Super P coating interlayer functioned as an upper current collector that increased the electrical conductivity, and abundant pyridinic N groups present in the cyclized cPAN matrix sequestered the PSs through strong interatomic attraction. Compared with the cell containing the uncoated PP separator, this modified PP separator design could synergistically immobilize PSs by chemisorption toward the cathode and reduce the initial activation barrier and overpotential. Furthermore, the PP Janus separator was highly efficient in preventing Li dendrite formation; additionally, the Li//Li symmetric cell containing the Janus separator extended the lifespan up to 1200 h. The electrochemical performance of the Li2S/r-GONR/CNT-based cell containing the cPAN/Super P-coated PP Janus separator improved, with an initial discharge capacity of 1059 mA h g–1 at 0.1C and 810 mA h g–1 at 1C. Additionally, the cell maintained a specific capacity of 439 mA h g–1 and exhibited improved capacity retention (68%) after 500 cycles at 3C. This showed that the cell based on the cPAN/Super P-modified PP Janus separator could effectively suppress the PS shuttle effect and prevent Li dendritic growth, thus improving the overall electrochemical performance of Li–S batteries.